American Globalization, 1492-1850 Trans-Cultural Consumption in Spanish Latin America - Yun Casalilla, Bartolomé; Berti, Ilaria; Svriz-Wucherer, Omar (Early Modern Iberian History in Global Contexts, 2021)
history of the Americas